Penerapan Outdoor Learning Untuk Meningkatkan Hasil Belajar Siswa Dalam Materi Tumbuhan Dan Bagian-Bagiannya Di SD Negeri 1 Panembahan - Rahman, Ghina Sheina; Wahyuningsih, Asih; Rochmah, Eliya (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2024)
This research aims to improve student learning outcomes in plant material and its parts through the implementation of Outdoor Learning at SD Negeri 1 Panembahan, Cirebon. This research uses a classroom action research (PTK) design which consists of two cycles, where each cycle includes planning, action, observation and reflection stages. The research results show that outdoor-based learning has great potential to be applied in the context of basic education, especially to improve student learning outcomes. With a significant increase in learning outcomes, it is hoped that this method can be integrated more widely in the school curriculum.